The Extent to Which Graduate Students at the College of Basic Education, University of Sulaimani, use Artificial Intelligence Programs in Their Academic Studies - حسين, أ.د .جواد نعمت حسين; عارف, أ.م.د. كارزان محمد عارف; Ahmad, Dr. Soran Hama Amin Ahmed (Sulaimani Journal for Humanities, 2025)
The study sought to determine the level of usage of the artificial intelligence program among College of Basic Education students of the University of Sulaymaniyah in the academic discipline. A descriptive-analytical method was used to achieve the study objectives, given the nature of the study material. The study sample comprised graduate students totaling 52 in number, with 39 master's and 13 doctoral students from the College of Basic Education of the University of Sulaymaniyah for the academic period of (2024-2025) in different scientific departments. The researchers applied a questionnaire scale of 32 items distributed in three constructs: the use of the artificial intelligence software in the preparation of the scientific research, the use of the artificial intelligence software in the completion of the academic tasks, and the attitudes of the students in using the artificial intelligence software in study and graduate studies. The psychometric properties of the questionnaire were identified, including validity, reliability, discrimination coefficient, and item internal consistency. Upon filling in the questionnaire by the study sample, statistically, the data were examined by appropriate statistical processes, including weighted mean calculations, t-tests, Pearson correlation coefficients, and other relevant analyses. The research reached several conclusions, the most important of which are: a) Artificial intelligence software usage in academic research by the graduate students was low. b) Students used several artificial intelligence programs during their academic studies. ChatGPT ranked first with (69.2%) usage, followed by Claude in second place with (50%), and DeepSeek in third place with (36.5%). c) There is diversity in the percentage of students utilizing the artificial intelligence program with respect to the gender and scientific department variables. d) Students utilize computer-aided programs and tools of artificial intelligence "sometimes" in preparing their research and scientific theses, and in doing assignments and courses in the academic coursework. e) Students' attitudes towards the adoption of the application of artificial intelligence programs and tools in teaching and education were overall fairly positive. The research concluded with a series of conclusions, suggestions, and future research recommendations.
Keywords: programs; postgraduate students; level; artificial intelligence